(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In this article envisaged the information security of internal and exsternal policy in Amir Temur’s state. There has talved about tne functions and responsibilities of agents in the spheres such as ensuring the peace and security, tne diplomatic relations and well-reighbourhood polic with other countries of Temur’s Empire.